1990
DOI: 10.3109/00498259009046872
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic studies on pentachlorophenol (PCP) in rats

Abstract: 1. The metabolism of pentachlorophenol in rats was studied. 2. Metabolites isolated from rat urine and identified were: 2,3,4,5-tetrachlorophenol, 2,3,4,6-tetrachlorophenol, 2,3,5,6-tetrachlorophenol, tetrachlorocatechol, tetrachlororesorcinol, trichlorohydroquinone, tetrachlorohydroquinone, and traces of trichloro-1,4-benzoquinone, and tetrachloro-1,4-benzoquinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…PCP is a pow-erful uncoupler of oxidative phosphorylation. In current reports it suggested that tetrachlorohydroquinone (TCHQ), as a metabolite of PCP in liver (Juhl et al, 1985;Renner and Hopfer, 1990), may enhance toxicity and carcinogenicity of PCP, since it is capable of inducing oxidative damage (Wang and Lin, 1995). The mechanisms of toxicity induced by PCP to mammals and humans have been studied in vivo and in vitro (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PCP is a pow-erful uncoupler of oxidative phosphorylation. In current reports it suggested that tetrachlorohydroquinone (TCHQ), as a metabolite of PCP in liver (Juhl et al, 1985;Renner and Hopfer, 1990), may enhance toxicity and carcinogenicity of PCP, since it is capable of inducing oxidative damage (Wang and Lin, 1995). The mechanisms of toxicity induced by PCP to mammals and humans have been studied in vivo and in vitro (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the unchanged parent molecule and its glucuronide and sulfate conjugates are found, as well as other metabolites. Interestingly, besides the formation of the reactive metabolite, tetrachloro-1,4-benzoquinone, other chlorinated phenols were also identified as metabolites of PCP (21). This was parallel with the identification of PCP as one of the metabolites of hexachlorobenzene (26).…”
Section: Introductionmentioning
confidence: 99%
“…We established using standards that at the retention time of PCP there were no interferences from 2,4,5-,2,4,6-and 3,4,5-trichlorophenols; 2,3,4,6-and 2,3,5,6-tetrachlorophenols; tetrachloro-p-hydroquinone and tetrachloro-p-benzoquinone which are metabolites excreted by mammals and some of them also by aquatic species (Renner and Hopfer 1990;Tjeerdema et al 1994). approximately after 72 hr.…”
Section: Resultsmentioning
confidence: 99%
“…The tubes were sealed and placed in a boiling water bath for 1 hr. This procedure is analogous to the one recommended by Renner and Hopfer (1990), and it was optimized in our laboratory for p-nitrophenol (Oneto et al , 1995). Once they were cool, the hydrolyzed solutions were treated with K2C03 until pH 10 was reached, and then acetylated by the procedure described previously.…”
Section: Methodsmentioning
confidence: 99%